Visionary Leadership Activities in Improving the Quality of Education - Zulfahmi, Teuku; Iskandar; Mulyadi, Said (Journal of Science and Science Education, 2024)
The realization of this quality of education can be started from the performance of the principal as the key holder who controls and manages all activities of his school. So the purpose of this study is to determine the implementation of the visionary leadership model, the visionary leadership model to improve the quality of education, and to find out what the advantages and obstacles are in implementing the visionary leadership model at SMPN 3 Meulaboh West Aceh. This type of research is descriptive research using a qualitative approach with research samples, namely the Principal, Vice Principal, Vice Principal of Curriculum, Vice Principal of Student Affairs, and teachers at SMP Negeri 3 Meulaboh using an interview question sheet instrument. The results of the study showed that the Principal's Visionary Leadership Model at SMP Negeri 3 Meulaboh has a strong role and a clear vision for the school he leads. The results of the Principal's Visionary Leadership in Improving the Quality of Education at SMP Negeri 3 Meulaboh are that the principal has succeeded in carrying out his leadership well because he has a strong role in managing the school, and a visionary principal is able to take advantage of existing opportunities and has a concept of achieving a directed and clear vision. The drawback is the workload on teachers and education personnel to be able to achieve the vision set by the principal.